2014
DOI: 10.1007/s00213-014-3596-0
|View full text |Cite
|
Sign up to set email alerts
|

The novel α7 nicotinic acetylcholine receptor agonist EVP-6124 enhances dopamine, acetylcholine, and glutamate efflux in rat cortex and nucleus accumbens

Abstract: These results suggest increased cortical DA, ACh, and Glu release, which may contribute to the ability of the α7 nAChR agonist, EVP-6124, to treat cognitive impairment and possibly other dimensions of psychopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…As expected for an a7 nAChR agonist, RG3487 increased dopamine and ACh release in the rat hippocampus and prefrontal cortex (Huang et al, 2014b). Similarly, encenicline increased dopamine and ACh, as well as glutamate release in the prefrontal cortex (Huang et al, 2014a). Tested in clinical trials in schizophrenia patients, RG3487 showed no significant improvement of the cognitive deficit associated with schizophrenia, but patients with moderate negative symptoms exhibited a significant improvement in their symptoms (Umbricht et al, 2014).…”
Section: Gts-21mentioning
confidence: 58%
See 1 more Smart Citation
“…As expected for an a7 nAChR agonist, RG3487 increased dopamine and ACh release in the rat hippocampus and prefrontal cortex (Huang et al, 2014b). Similarly, encenicline increased dopamine and ACh, as well as glutamate release in the prefrontal cortex (Huang et al, 2014a). Tested in clinical trials in schizophrenia patients, RG3487 showed no significant improvement of the cognitive deficit associated with schizophrenia, but patients with moderate negative symptoms exhibited a significant improvement in their symptoms (Umbricht et al, 2014).…”
Section: Gts-21mentioning
confidence: 58%
“…Development of compounds acting at the a7 nAChR might therefore also serve to alleviate NMDA receptor dysfunction, as hypothesized in schizophrenia. Indeed, glutamate release from prefrontal cortex was elevated after treatment with a7 nAChR agonists in rats and nonhuman primates Huang et al, 2014a). The recent hypothesis that ketamine might be used for the treatment of depression indicates that in view of the a7 nAChR/NMDA receptor interaction, additional targets might be envisaged to treat a wide range of psychologic afflictions.…”
Section: B Schizophreniamentioning
confidence: 99%
“…Glutamatergic terminals express presynaptic α7 nAChRs in the rat VTA and PFC (Jones and Wonnacott, 2004, Huang et al, 2014). As shown in Figure 1, glutamate release via stimulating presynaptic α7 nAChRs in glutamate terminals may have an indirect action in dopamine release by activating ionotropic glutamate receptors (iGLURs) in dopaminergic terminals (Desce et al, 1992, Fu et al, 2000, Kaiser and Wonnacott, 2000).…”
Section: Role Of Nicotinic Acetylcholine Receptors In the Modulatimentioning
confidence: 99%
“…Increased dopamine release within this pathway may target the negative symptoms of the disease [36]. Agonists targeting the alpha7 nicotinic acetylcholine receptor (a7-nAChR) increase dopamine release in both pathways [37,38]. While increased dopamine release in the mesocortical pathway could potentially improve emotional blunting and cognitive symptoms, increase dopamine release within the mesolimbic pathway could potentially exacerbate hallucinations.…”
Section: Nicotinic Receptors and Schizophreniamentioning
confidence: 99%